2015
DOI: 10.2334/josnusd.57.335
|View full text |Cite
|
Sign up to set email alerts
|

Association of periodontal status with liver abnormalities and metabolic syndrome

Abstract: Although an association between periodontal status and liver abnormalities has been reported, it has not been described in relation to metabolic syndrome (MetS), which often coexists with non-alcoholic fatty liver disease. We examined the association of a combination of liver abnormality and MetS with periodontal condition in Japanese adults, based on the level of alcohol consumption. In 2008, 4,207 males aged 45.4 ± 8.9 years and 1,270 females aged 45.9 ± 9.7 years had annual workplace health check-ups at a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Although still debated, long‐term use of asthma medication may put patients at risk for dental caries, dental erosion, and periodontitis . While it is important to consider behavioral patterns for an association between oral health outcome and liver disease, periodontitis has also been linked to liver abnormalities among males who consume little to no alcohol in the past as well . Indeed, diabetes may be acting as a confounding factor for the association between the oral health outcome, coronary heart disease, and congestive heart disease as diabetic patients have been found to be at higher risk of congenital heart disease, and congestive heart failure .…”
Section: Discussionmentioning
confidence: 99%
“…Although still debated, long‐term use of asthma medication may put patients at risk for dental caries, dental erosion, and periodontitis . While it is important to consider behavioral patterns for an association between oral health outcome and liver disease, periodontitis has also been linked to liver abnormalities among males who consume little to no alcohol in the past as well . Indeed, diabetes may be acting as a confounding factor for the association between the oral health outcome, coronary heart disease, and congestive heart disease as diabetic patients have been found to be at higher risk of congenital heart disease, and congestive heart failure .…”
Section: Discussionmentioning
confidence: 99%
“…In the elderly population, it is important to reduce the risk of systemic disease by controlling risk factors at an early stage. A number of researchers have suggested that periodontal disease may be a risk factor for systemic diseases such as cardiovascular disease, rheumatoid arthritis and metabolic syndrome (Ahmad et al., ; Furuta et al., ; Hanindriyo, Yoshihara, Hirotomi, & Miyazaki, ; Iwasaki et al., ; Pussinen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…and metabolic syndrome (Ahmad et al, 2015;Furuta et al, 2016;Hanindriyo, Yoshihara, Hirotomi, & Miyazaki, 2013;Iwasaki et al, 2016;Pussinen et al, 2003).…”
mentioning
confidence: 99%
“…In addition, the incidence of periodontal disease in healthy Japanese women was reported to be significantly increased with elevated serum levels of AST, ALT, and cholinesterase [38]. Furthermore, an observational study with annual workplace health check-ups at a company in Japan reported an association between periodontal condition and the combination of elevated ALT and metabolic syndrome (MetS) in men [39]. Besides, it has been suggested that more severe periodontal disease is associated with increased serum levels of GGT, a liver biochemical parameter, in Japanese adults with no alcohol-drinking habits [40].…”
Section: Discussionmentioning
confidence: 99%